Feasibility of implementing pranic healing as a complementary service: A case study at Sanglah General Hospital, Denpasar - Megawati, Desak Made; Lubis, Dinar Saurmauli; Manuaba, Ida Bagus Gede Fajar; Lesmana, Cokorda Bagus Jaya (Universitas Udayana, 2021)
Background and purpose: WHO supports the implementation of complementary therapy services in health facilities to increase comprehensive health services coverage. Sanglah Hospital is developing the pranic healing service as part of the development of Indonesia’s medical tourism and traditional health. This study aims to determine the extent to which the feasibility, obstacles, challenges, and opportunities of the pranic healing service implemented at Sanglah Hospital. Methods: This study employed a mixed-methods design with a case study approach. The data were collected from March to April 2020 using in-depth interview with 23 informants by collecting information on acceptance, readiness, requests, and service management. Documents and archival records were also collected. The survey data were collected using a selfadministered questionnaire from 40 respondents by collecting information on patients’ requests and acceptance aspects. The qualitative data analysis was performed thematically and presented in a narrative form. The survey data were analyzed using univariate analysis. Results: The pranic healing service received support from the Ministry of Health and the hospital management, had a good acceptance from health workers and patients, was the only complementary service of its kind in health facilities throughout Indonesia and had the potential for the development of medical tourism. Obstacles and challenges found were related to workforce management, regulatory readiness, referral systems, and the development of inpatient services. Conclusion: Pranic healing service could be implemented at Sanglah Hospital because they had substantial support and because of demand and acceptance aspects. However, obstacles and challenges on the implementation and practicality aspects should be overcome for the sustainability of this service. The pranic healing has a good potency since to date, it is the only one available in Indonesia which is also potential for the development of medical tourism.